2011
DOI: 10.1136/adc.2010.203992
|View full text |Cite
|
Sign up to set email alerts
|

A right-to-left shunt in children with arterial ischaemic stroke

Abstract: Both the prevalence of RLS and number of detected MES were significantly higher in a group of children with AIS and prothrombotic disorders or with AIS of undetermined aetiology compared to controls. These findings suggest that paradoxical embolism may be an underestimated cause of AIS in children, particularly those with AIS and prothrombotic disorders or with AIS of undetermined aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…In our pilot study (Dowling, et al, 2010), retrospective chart review found potential shunting in 11.7% (7/60) of children with stroke who did not have SCD (excluding children with known congenital heart disease). Benedik et al (2011) reported on transesophageal echocardiograms with contrast as well as using contrasted transcranial Doppler ultrasonography and reported potential shunting in 7/26 (27%) of controls compared with 11/23 (48%) of children with stroke or TIA (without SCD), excluding those with other identified aetiologies for stroke. Intrapulmonary shunting alone was an independent predictor of cryptogenic stroke or TIA in adults without SCA compared to controls (OR 2.6 (CI 1.6–4.2)) (Abushora, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In our pilot study (Dowling, et al, 2010), retrospective chart review found potential shunting in 11.7% (7/60) of children with stroke who did not have SCD (excluding children with known congenital heart disease). Benedik et al (2011) reported on transesophageal echocardiograms with contrast as well as using contrasted transcranial Doppler ultrasonography and reported potential shunting in 7/26 (27%) of controls compared with 11/23 (48%) of children with stroke or TIA (without SCD), excluding those with other identified aetiologies for stroke. Intrapulmonary shunting alone was an independent predictor of cryptogenic stroke or TIA in adults without SCA compared to controls (OR 2.6 (CI 1.6–4.2)) (Abushora, et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In RCTs only patients over 18 years old were included [3][4][5]. According to another publication by Benedik et al [23], transcatheter PFO closure in children is a relatively safe and effective procedure, which also makes it possible to discontinue long-lasting antithrombotic treatment, which is usually hard to maintain because of poor compliance and possible side effects. In our study the procedure was successfully completed in all patients, and no procedure-related complications were observed during hospitalisation.…”
Section: Discussionmentioning
confidence: 99%
“…Predisposing conditions for ischemic cerebrovascular accidents in children include congenital heart malformations (congenital cyanotic complex heart malformations or acquired heart disease), sickle cell disease, infections, and collagen tissue abnormalities [13], but around half occur in children who were previously well (cryptogenic stroke) [14]. It is well known from literature, that one of the most common conditions associated with AIS is congenital heart malformations (like patent foramen ovale) [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Etiologymentioning
confidence: 99%
“…While there is some evidence suggesting an important role of right-to-left shunting across an atrial defect, particularly among patients with prothrombotic conditions or cryptogenic stroke [10], the role of device closure remains undefined due to lack of sufficient evidence [11].…”
Section: Introductionmentioning
confidence: 99%